Revisiting the techno-economic analysis process for building-mounted, grid-connected solar photovoltaic systems: Part two - Application. (July 2017) - Sommerfeldt, Nelson; Madani, Hatef
Abstract: Part One in this two part paper identified Monte Carlo analysis as an improved approach over traditional deterministic techno-economic methods for solar PV prosumers in deregulated markets. In this paper a novel Monte Carlo methodology is described and demonstrated through a case study for the Swedish residential sector, which includes a review of relevant market, climate, and policy conditions, their use in determining inputs, and the probabilistic results. The probability of profitability (PoP) is introduced as an indicator in conjunction with result distributions. The results show that under current policy conditions, Swedish PV investors with well positioned buildings have a 71% chance of making a 3% real return on investment, and virtually no chance of losing their original investment. Without subsidies the PoP drops to 8%. In none of the simulated cases was any of the original investment lost. The PoP is most sensitive to the capital subsidy and the uncertainty of market based, long-term support is less critical to the chances of a successful investment. Given the current market conditions, Swedish PV prosumers can expect a return on investment. The decision to install will also depend on the probability of achieving their desired profitability, which Monte Carlo analysis quantifies well. Highlights: A novel Monte Carlo analysis methodology is described. A case study considering the Swedish residential sector is used as a demonstration. The probability of profitability is introduced as an economic indicator. Current subsidies makes profitability likely, mostly due to capital rebates.